Perception of organizational change toward employees’ performance of FGV Tembangau 9 / Muhammad Nur Rahman Abd Razak - Abd Razak, Muhammad Nur Rahman (Faculty of Plantation and Agrotechnology, 2019)
Organizational change is a field of the board hypothesis that centers around the phases that organizations experience as they develop. It happens when an organization makes a progress from its present state to some ideal future state. All associations experience continuous change, and concentrate the manners in which associations change gives point of view on the procedure. In this study, I will going to focus on organizational change in a plantation company, FGV Tembangau 9. Perception of organizational change towards employees’ performance could be the precise title for this study. The point of this investigation is to decide the view of authoritative change towards specialists' execution in estate of FGV Tembangau 9. Four factors that will be considered which are communication, employee development, tolerance to change and leadership. The objective of this study is to examine the relationship between the factors of organizational change towards employees’ performance and to determine the most dominant factor of organizational change that contribute to employees’ performance. The study was focused on the senior workers which have more experience to the change. A survey was conducted to 52 sample of 60 populations in achieving the objectives. Data collected were analysed for correlation and multiple linear regression by using Statistical Package for the Social Science (SPSS). The result obtained from this study was all of the factors has a significant relationship since p-value is less than 0.05. Through regression analysis, it found that the most dominant factor of perception of organizational change towards employees’ performance was tolerance to change. I hope this study can be a guideline for plantation companies to improve their management quality.